Defective HLA Class I Expression and Patterns of Lymphocyte Infiltration in Chordoma Tumors. Issue 6 (June 2021) - Patel, Shalin S.; Nota, Sjoerd P.; Sabbatino, Francesco; Nielsen, G. Petur; Deshpande, Vikram; Wang, Xinhui; Ferrone, Soldano; Schwab, Joseph H.
Abstract: Background: There are no effective systemic therapies for chordoma. The recent successes of immunotherapeutic strategies in other cancers have resulted in a resurgence of interest in using immunotherapy in chordoma. These approaches rely on a functional interaction between the host's immune system and the expression of tumor peptides via the human leukocyte antigen (HLA) Class I antigen. It is not known whether chordoma cells express the HLA Class I antigen. Questions/purposes: (1) Do chordoma tumors exhibit defects in HLA Class I antigen expression? (2) What is the pattern of lymphocyte infiltration in chordoma tumors? Methods: Patients with chordoma treated at Massachusetts General Hospital between 1989 and 2009 were identified with permission from the institutional review board. Of the 75 patients who were identified, 24 human chordoma tumors were selected from 24 distinct patients based on tissue availability. Histology slides from these 24 formalin-fixed paraffin-embedded chordoma tissue samples were deparaffinized using xylene and ethanol and underwent heat-induced antigen retrieval in a citrate buffer. Samples were incubated with monoclonal antibodies directed against HLA Class I antigen processing machinery components. Antibody binding was detected via immunohistochemical staining. Staining intensity (negative, weakly positive, strongly positive) was assessed semiquantitatively and the percentage of chordoma cells stained for HLA Class I antigen subunits was assessed quantitatively. Hematoxylin and eosin-stained histology slides from the same 24 chordoma samples were assessed qualitatively for the presence of tumor-infiltrating lymphocytes and histologic location of these lymphocytes. Immunohistochemical staining with monoclonal antibodies directed against CD4 and CD8 was performed in a quantitative manner to identify the lymphocyte subtype present in chordoma tumors. All results were scored independently by two investigators and were confirmed by a senior bone and soft tissue pathologist. Results: Seven of 24 chordoma samples exhibited no staining by the anti-HLA-A heavy chain monoclonal antibody HC-A2, two had weak staining intensity, and eight had a heterogeneous staining pattern, with fewer than 60% of chordoma cells exhibiting positive staining results. Four of 24 samples tested were not stained by the anti-HLA-B/C heavy chain monoclonal antibody HC-10, five had weak staining intensity, and 11 displayed a heterogeneous staining pattern. For the anti-β-2-microglobulin monoclonal antibody NAMB-1, staining was detected in all samples, but 11 had weak staining intensity and four displayed a heterogeneous staining pattern. Twenty-one of 24 samples tested had decreased expression in at least one subunit of HLA Class I antigens. No tumors were negative for all three subunits. Lymphocytic infiltration was found in 21 of 24 samples. Lymphocytes were primarily found in the fibrous septae between chordoma lobules but also within the tumor lobules and within the fibrous septae and tumor lobules. Twenty-one of 24 tumors had CD4+ T cells and 11 had CD8+ T cells. Conclusion: In chordoma tissue samples, HLA Class I antigen defects commonly were present, suggesting a mechanism for escape from host immunosurveillance. Additionally, nearly half of the tested samples had cytotoxic CD8+ T cells present in chordoma tumors, suggesting that the host may be capable of mounting an immune response against chordoma tumors. The resulting selective pressure imposed on chordoma tumors may lead to the outgrowth of chordoma cell subpopulations that can evade the host's immune system. Clinical Relevance: These findings have implications in the design of immunotherapeutic strategies for chordoma treatment. T cell recognition of tumor cells requires HLA Class I antigen expression on the targeted tumor cells. Defects in HLA Class I expression may play a role in the clinical course of chordoma and may account for the limited or lack of efficacy of T cell–based immunity triggered by vaccines and/or checkpoint inhibitors.